Exploring the influence of islamic spiritual intelligence, emotional intelligence on students leadership competencies with islamization of knowledge as a mediating factor - Solih, Mohamed (Kulliyyah of Education, International Islamic University Malaysia, 2021)
International Islamic University has been championing the Islamization of Human Knowledge (IOHK) with the goal of contributing to the holistic development of human capital. This strategy will enhance the good impact that students will have on society as their mentality is shaped on Islamic Spiritual Intelligence (ISI) and their emotions are trained within the scope of the Islamic world view. Thus, this study has attempted to evaluate the model of Leadership Competencies of Student Leaders. Specifically, the causal relationships between Emotional Intelligence (EI), Islamic Spiritual Intelligence (ISI), and Leadership Competencies of Student Leaders (LCSL), mediating through IOHK in three campuses of IIUM were tested. The current study employed a quantitative cross-sectional survey with a stratified random sampling technique. The data were collected using a self-administered questionnaire, distributed to 372 student leaders in the year 2018 /2019. There were six research questions and seven research hypotheses formulated. The collected data were analyzed using descriptive statistics for research question one; Confirmatory Factor Analysis (CFA) for research question two and hypothesis one; and, a full-fledged Structural Equation Modeling (SEM) for research questions three to six and hypotheses two to seven. The results from the descriptive analysis revealed that student leaders' practice and perception of IOHK (78%), EI (78%), ISI (91%), and LCSL (79%) exceeded 50%. Additionally, the CFA results indicated that the instrument used in the study was psychometrically sound in terms of convergent, discriminant, and composite validity. The full-fledged SEM showed that the hypothesized model exhibited relationships between observed variables and IOHK, ISI, EI, and LCSL. It also highlighted that EI, ISI exerted significant positive influence on Leadership Competencies of Student Leaders both directly and indirectly. However, IOHK mediated partially between EI and LCSL and mediated fully between ISI and LCSL. This study contributes to the models and frameworks of Jumahata's (2016) Islamic Spiritual Intelligence, Goleman's (1999) Emotional Intelligence, Hassan's (2010) "Man of Sound Reasoning” of Islamization of Human Knowledge, and the frameworks of Seemiller's (2013) Student Leadership Competencies together and Park, Jeong, Jang, Yoon, and Lim's (2018) Integrative global leadership to develop young leaders respectively. This study further contributes to the methodologies to evaluate the competence of these leaders. Furthermore, it draws more guidelines to parents and stakeholders to nurture the youth by inculcating the values and resilience needed to survive as a good leader in the 21st century.